Mitigation, Apology and the Quantification of Non-Pecuniary Damages - Berryman, Jeff (2017)
English Abstract: The law has historically granted damages for some forms of non-pecuniary losses. In doing so, courts have freely admitted that there is imprecision in quantifying such losses and that there is no quantitative and objective calculus on pain and suffering. Against this background, new research on how hedonic losses are experienced by a victim provide an opportunity to review how non-pecuniary losses should be compensated. Some of this research suggests that experiences of anxiety, frustration and suffering may not affect a victim’s happiness as great as is presupposed in current models of compensation, and further, that its impact may also be ameliorated by the offering of an apology. In this essay, the author asks whether the law can incentivize tortfeasors to offer an apology as an element in mitigating compensatory damages for non-pecuniary loss.
Keywords: Jeff Berryman